The combined formulation of brassinolide and pyraclostrobin increases biomass and seed yield by improving photosynthetic capacity in Arabidopsis thaliana - An, Ya-Qi; Qin, Zi-Ting; Li, Dan-Dan; Zhao, Rui-Qi; Bi, Bo-Shi; Wang, Da-Wei; Ma, De-Jun; Xi, Zhen (Frontiers in Plant Science, 2023)
In the context of global food crisis, applying the phytohormone-brassinosteroids (BRs) in combination with the fungicide-pyraclostrobin (Pyr) was beneficial for plant quality and productivity in several field trials. However, in addition to the benefits of disease control due to the innate fungicidal activity of Pyr, it remains to be understood whether the coapplication of BL+ Pyr exerts additional growth-promoting effects. For this purpose, the effects of BL treatment, Pyr treatment, and BL+ Pyr treatment in Arabidopsis thaliana were compared. The results showed that the yield increased at a rate of 25.6% in the BL+Pyr group and 9.7% in the BL group, but no significant change was observed in the Pyr group. Furthermore, the BL+Pyr treatment increased the fresh weight of both the leaves and the inflorescences. In contrast, the Pyr and BL treatments only increased the fresh weight of leaves and inflorescences, respectively. Additionally, the BL + Pyr treatment increased the Pn, Gs, Tr, Vc, max, Jmax, VTPU, ETR, Fv’/Fm’, ΦPSII, Rd, AYE and Rubisco enzyme activity by 26%, 38%, 40%, 16%, 19%, 15%, 9%, 10%, 17%, 179%, 18% and 32%, respectively. While, these paraments did not change significantly by the BL or Pyr treatments. Treatment with BL + Pyr and Pyr, rather than BL, improved the chlorophyll a and chlorophyll b contents by upregulating genes related to chlorophyll biosynthesis and downregulating genes related to chlorophyll degradation. Additionally, according to transcriptomic and metabolomic analysis, the BL+ Pyr treatment outperformed the individual BL or Pyr treatments in activating the transcription of genes involved in photosynthesis and increasing sugar accumulation. Our results first validated that the combined usage of BL and Pyr exerted striking synergistic effects on enhancing plant biomass and yield by increasing photosynthetic efficiency. These results might provide new understanding for the agricultural effects by the co-application of BL and Pyr, and it might stimulate the efforts to develop new environment-friendly replacement for Pyr to minimize the ecotoxicology of Pyr.